The Impact of COVID-19 Infection on Abdominal Aortic Aneurysms: Mechanisms and Clinical Implications - Zenghan Cao; Jianhang Gao; Jianqiang Wu; Yuehong Zheng (Hindawi-Wiley, 2024)
Conclusion: COVID-19 infection can influence the onset and progression of aortic aneurysms by affecting the RAAS, triggering inflammation and immune dysregulation in the arterial wall, and inducing a hypercoagulation state. It is crucial to comprehensively understand the impact of pandemic viral infections on aortic diseases at the foundational and clinical levels, thereby identifying potential preventative or therapeutic approaches and preparing for potential future outbreaks.